On the finite time stabilization via robust control for uncertain disturbed systems - Ordaz, Patricio; Alazki, Hussain; Sánchez, Bonifacio; Ordaz-Oliver, Mario (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with the finite-time stabilization problem for a class of uncertain disturbed systems using linear robust control. The proposed algorithm is designed to provide the robustness of a linear feedback control scheme such that system trajectories arrive at a small-size attractive set around an unstable equilibrium in a finite time. To this end, an optimization problem with a linear matrix inequality constraint is presented. This means that the effects of external disturbances, as well as matched and mismatched uncertain dynamics, can be significantly reduced. Finally, the performance of the suggested closed-loop control strategies is shown by the trajectory tracking of an unmanned aerial vehicle flight.
Keywords: finite time bounded stability; uncertain disturbed systems; robust stabilization; ultimate bound minimization